The Therapeutic Effect of Adipose-Derived Mesenchymal Stem Cells for Radiation-Induced Bladder Injury - Qiu, Xuefeng (Stem Cells Int, 2016)
This study was designed to investigate the protective effect of adipose derived mesenchymal stem cells (AdMSCs) against radiation-induced bladder injury (RIBI). Female rats were divided into 4 groups: (a) controls, consisting of nontreated rats; (b) radiation-treated rats; (c) radiation-treated rats receiving AdMSCs; and (d) radiation-treated rats receiving AdMSCs conditioned medium. AdMSCs or AdMSCs conditioned medium was injected into the muscular layer of bladder 24 h after radiation. Twelve weeks after radiation, urinary bladder tissue was collected for histological assessment and enzyme-linked immunosorbent assay (ELISA) after metabolic cage investigation. At the 1 w, 4 w, and 8 w time points following cells injection, 3 randomly selected rats in RC group and AdMSCs group were sacrificed to track injected AdMSCs. Metabolic cage investigation revealed that AdMSCs showed protective effect for radiation-induced bladder dysfunction. The histological and ELISA results indicated that the fibrosis and inflammation within the bladder were ameliorated by AdMSCs. AdMSCs conditioned medium showed similar effects in preventing radiation-induced bladder dysfunction. In addition, histological data indicated a time-dependent decrease in the number of AdMSCs in the bladder following injection. AdMSCs prevented radiation induced bladder dysfunction and histological changes. Paracrine effect might be involved in the protective effects of AdMSCs for RIBI.